2011
DOI: 10.1074/jbc.m111.255075
|View full text |Cite
|
Sign up to set email alerts
|

Snapshots of Enzymatic Baeyer-Villiger Catalysis

Abstract: Baeyer-Villiger monooxygenases catalyze the oxidation of carbonylic substrates to ester or lactone products using NADPH as electron donor and molecular oxygen as oxidative reactant. The emerging picture is that these enzymes are mainly oxygen-activating and "Criegee-stabilizing" catalysts that act on any chemically suitable substrate that can diffuse into the active site, emphasizing their potential value as toolboxes for biocatalytic applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
95
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(99 citation statements)
references
References 39 publications
4
95
0
Order By: Relevance
“…50 Here, we showed that the positively charged His396 of C 2 acts as a general acid for proton-coupled electron transfer to activate O 2 . Another enzyme that catalyzes the same reaction as the C 2 , the oxygenase component of 4-hydroxyphenylacetate 3-monooxygenasefrom Thermus thermophilus HB8 (HpaB), 51 has an Arg residue (Arg100) located ~4.8 Å from C4a.…”
Section: Discussionmentioning
confidence: 95%
“…50 Here, we showed that the positively charged His396 of C 2 acts as a general acid for proton-coupled electron transfer to activate O 2 . Another enzyme that catalyzes the same reaction as the C 2 , the oxygenase component of 4-hydroxyphenylacetate 3-monooxygenasefrom Thermus thermophilus HB8 (HpaB), 51 has an Arg residue (Arg100) located ~4.8 Å from C4a.…”
Section: Discussionmentioning
confidence: 95%
“…23 Following the publication of these three structures, reports of several more PAMO structures, in complex with NADP + as well as a weak inhibitor, were solved. 24 The PAMO structures allowed the comparison of the oxidized and reduced states of FAD. In addition, a series of structures of 2-oxo-Δ 3 -4,5,5-trimethylcyclopentenylacetyl-coenzyme A monooxygenase (OTEMO) 25 were solved, representing the first BVMO crystal structures of a dimeric BVMO, and also of a BVMO that acts on a very large substrate.…”
mentioning
confidence: 99%
“…) readily perform such transformations lend to speculate that there are still more intricate details influencing BVMO promiscuity in the reaction mechanism [24] of the enzymatic Baeyer-Villiger oxidation that have not been understood so far.…”
Section: Scoring Results Of Bvmosmentioning
confidence: 97%